Environmental risk management: Fostering sustainable development through education - Walter, Miroslav; Jovičić, Nives; Skendrović, Kruno (Crisis Management Days, 2024)
Education plays a crucial role in shaping environmental protection awareness, starting from preschool age to higher education. Through systematic learning about environmental issues and sustainable practices, individuals gain an understanding of the complexity of the ecological challenges facing the planet. In addition to formal education, continuous public environmental awareness development through media and alternative channels is crucial for spreading awareness of environmental issues and fostering action at all societal levels. Improving environmental awareness could help reduce risks and benefit the planet. This paper examines the importance of raising awareness to address environmental challenges. Implementing the paradigm of sustainable development into the environmental awareness of children and adults is a complex and time-consuming process. The emphasis is on raising the level of environmental awareness through the educational system, and research conducted among students at Velika Gorica University highlighted the need for systematic education on environmental awareness at all levels, from preschool to adulthood.